2013
DOI: 10.1039/c3cc41627e
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of electron transfer rates of different facets on single gold nanoparticles during catalytic reactions

Abstract: Rayleigh scattering spectra of high-index {730} elongated tetrahexahedral gold nanoparticles and low-index {100}, {110}, and {111} gold nanorods were collected in real time in the reduction of 4-nitrophenol. The high-index facets are capable of accepting electrons seven times faster and emitting electrons two-and-a-half times faster than low-index facets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The high-index facets both accept electrons and emitted electrons faster than that of low-index facets. Thus, the higherindex facets function was more efficient in 4-NP catalytic reduction [103].…”
Section: Anisotropic Aunps For 4-np Reductionmentioning
confidence: 99%
“…The high-index facets both accept electrons and emitted electrons faster than that of low-index facets. Thus, the higherindex facets function was more efficient in 4-NP catalytic reduction [103].…”
Section: Anisotropic Aunps For 4-np Reductionmentioning
confidence: 99%
“…It has mostly been suggested that gold nanoparticles could catalyze this reaction by facilitating electron transfer from BH 4 − to 4-NP (Scheme 1), and the kinetics can be treated in terms of the Langmuir-Hinshelwood (LH) model [17,18]. A change in temperature does not drive a change in mechanism, thus allowing researchers to measure the activation energy of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…It has been recognized the catalytic activity of a nanoparticle depends not only on its chemical composition and size, but also atomic scale structure, including edges (confined electromagnetic fields) 14, 30, 104, 107 and facets (reduced activation energy). 11 Tools that could perform in situ characterization of both the atomic scale structure and catalytic activity of each individual nanoparticles would significantly advance the field.…”
Section: Perspectivementioning
confidence: 99%
“…9 By analyzing over 100 nanoparticles, Kim et al 10 discovered a correlation between the maximum extinction wavelength of a single AuNR and its sensitivity to a change in the surrounding refractive index. Yi et al 11 studied the evolution of optical scattering spectrum of Au nanoparticle-catalyzed reduction of 4-nitrophenol, and observed faster electron transfer rates in high-index elongated tetrahexahedral Au nanoparticles compared with those of low-index AuNRs. The size of a nanoparticle also affects its properties.…”
mentioning
confidence: 99%